Odpowiedzi

2009-12-28T20:16:17+01:00
336cm2-264cm2=72cm2
72cm2/2=36cm2 <2 podstawy>
<pierwiastek> z 36=6cm

264cm2/4=66cm2
66cm2/6cm=11cm

h=11cm
1 5 1
2009-12-28T20:24:57+01:00
Pc=336cm²
Pb=264cm
h=?
Pc=Pp+Pb
336=Pp+264
Pp=336-264=72
Pp=2a²/:2
36=a²
a=6
Pb=4ah
264=4x6xh
264=24h
h=11

Sprawdzenie:
Pb=4ah
Pb=4x6x11=264
I się zgadza;p
1 5 1
2009-12-28T21:04:52+01:00
Pc=2Pp+Pb
Pc=336 cm2
Pb=264cm2

2Pp+Pb=336
2Pp+264=336
2Pp=72 /:2
Pp=36

Pp=a2
a2=36
a=6

Pb=4*6*h
264=24h /:24
11=h

Wysokość tego graniastosłupa wynosi 11 cm